2021
DOI: 10.3390/s21196643
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Measurement of Loading Forces with High-Speed Camera

Abstract: In the last few decades, there has been a significant increase in interest in developing, constructing, and using structural health monitoring (SHM) systems. The classic monitoring system should, by definition, have, in addition to the diagnostic module, a module responsible for monitoring loads. These loads can be measured with piezoelectric force sensors or indirectly with strain gauges such as resistance strain gauges or FBG sensors. However, this is not always feasible due to how the force is applied or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The analysis revealed that several sensors had been used for validation purposes, including laser displacement sensors [32,34,41,42,49,70,74,76,82], accelerometers [32][33][34]50,51,53,55,59,61,[64][65][66][67][68]76], IMU [60], linear variable differential transformers [34,36,41,50,54,61,66,67,73], laser Doppler vibrometers [38,46], stationary cameras [42,75,83], actuators [71], laser trackers [81], infrared sensors [48], and marker-based systems [44,73]. Marker-based systems are routinely used in other fields (such as medicine), where they are the traditional reference systems for motion capture and analysis.…”
Section: Validation With Gold-standardmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis revealed that several sensors had been used for validation purposes, including laser displacement sensors [32,34,41,42,49,70,74,76,82], accelerometers [32][33][34]50,51,53,55,59,61,[64][65][66][67][68]76], IMU [60], linear variable differential transformers [34,36,41,50,54,61,66,67,73], laser Doppler vibrometers [38,46], stationary cameras [42,75,83], actuators [71], laser trackers [81], infrared sensors [48], and marker-based systems [44,73]. Marker-based systems are routinely used in other fields (such as medicine), where they are the traditional reference systems for motion capture and analysis.…”
Section: Validation With Gold-standardmentioning
confidence: 99%
“…This choice applies to the following studies: [34,[40][41][42]44,45,[48][49][50][51][53][54][55][58][59][60][61][62][63][64]66,67,[69][70][71][72][73][74][75][76][77][78][80][81][82]. In a few cases, the experimental scenarios were outdoors where, on the other hand, it was necessary to consider, at least in part, the environmental conditions and the problems previously indicated, testing the solution on scale models in most cases as well.…”
Section: Experimental and Real-world Scenariosmentioning
confidence: 99%
“…The load is very important for the fatigue life of dropper and the health of catenary suspension structure, and the use of sensor measurement will change the structure of catenary and threaten the operation safety of high-speed railway. Mendrok et al 19 propose a contactless measurement method based on high-speed camera to identify the load on the object, and the correctness of the method is verified by experiments. Jiang et al 20 based on a coarse subset and line search designed a portable detection device which can accurately identify the uplift amount of contact line under different background environments; and it shows that it is feasible to measure and analyze the vibration displacement of catenary suspension based on high-speed camera.…”
Section: Introductionmentioning
confidence: 99%